ASB9 promotes ubiquitin-mediated degradation of TNP2 to facilitate histone-to-protamine transition in humans and mice - Shikun Zhao; Gan Shen; Tiechao Ruan; Liangchai Zhuo; Yan Wang; Xiang Wang; Yunchuan Tian; Xinyao Tang; Jun Ma; Xiaohui Jiang; Yingteng Zhang; Chuan Jiang; et al. (Proceedings of the National Academy of Sciences, 2026)
During spermiogenesis, nuclear remodeling occurs where histones are sequentially replaced by transition proteins (TNPs) and protamines, a process essential for sperm maturation. Although the degradation of histones and TNPs is thought to be essential for sperm nuclear remodeling, the underlying mechanisms, particularly those governing TNP degradation, remain poorly understood. In this study, we investigated the role of the ankyrin repeat-containing SOCS box protein 9 (ASB9) during spermiogenesis and found that its deficiency causes TNP2 retention, leading to a failure of the histone-to-protamine transition in both humans and mice. This disruption consequently causes male infertility, characterized by sperm head malformation and impairments in fertilization and early embryonic development. Mechanistically, we found that ASB9 assembles a testis-specific Cullin-RING ligase (CRL) complex—TNP2–ASB9–ELOB/C–CUL5–RBX1—that mediates the ubiquitin-dependent degradation of TNP2 to facilitate the histone-to-protamine transition during spermiogenesis. Collectively, our study uncovers the mechanism underlying TNP2 degradation and highlights the critical role of ASB9 in male fertility through the CRL complex-mediated ubiquitination pathway, thereby expanding the fundamental understanding of nuclear remodeling during spermiogenesis.